Esophageal pH Testing in Patients Refractory to Proton Pump Inhibitor Therapy - Barbara A MacKalski; Alexandra Ilnyckyj (Canadian Journal of Gastroenterology)
BACKGROUND: Proton pump inhibitors (PPIs) are the most potent drugs available for the management of gastroesophageal reflux disease (GERD). Ambulatory 24 h pH monitoring is often recommended for patients experiencing symptoms despite PPI therapy. Recent pivotal data suggest that pH studies are predictably normal in this setting, casting doubt on the clinical utility of the current practice.